2019
DOI: 10.1021/acs.iecr.9b01604
|View full text |Cite
|
Sign up to set email alerts
|

High Aluminum Content Beta Zeolite as an Active Lewis Acid Catalyst for γ-Valerolactone Decarboxylation

Abstract: Butene plays an essential role in the area of petrochemical industry. The production of butene from the biomass-derived platform molecule γ-valerolactone (GVL) is of great interest. GVL decarboxylation reaction occurred under high temperature because the catalytic activity of the catalysts used before was not efficient for this reaction. In this work, beta zeolite with Si:Al = 5 was synthesized and used for GVL decarboxylation. It exhibited a higher catalytic performance than other commercial zeolites due to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…Ionic liquids (ILs) are thus the ideal solvents due to their lack of (or extremely low) vapor pressure, miscibility with polymers as well as organic compounds and metal catalysts (which makes most homogeneous catalytic reactions feasible), and high stability ranging from −30 to 300 °C. These promising characteristics of ILs enable us to consider them as desirable solvents for synthesis of high-molecular-weight polyesters in the ADMET condensation polymerization. Although olefin metathesis reactions in ILs have been known, the reported examples of ADMET polymerization have been limited so far. , For instance, the polymerization of 1,9-decadiene in 1- n -butyl-3-methyl imidazolium hexafluorophosphate ([Bmim]­PF 6 ,) in the presence of RuCl 2 (PCy 3 ) 2 (CHPh) ( G1 ) at 50 °C afforded rather high molecular weight polymers (Scheme , M n = 1.08–1.92 × 10 4 ) . The polymerization of 1,4-bis­(undec-10-en-1-yloxy)-triptycene conducted at 100 °C using G2 (initially 80 °C for 24 h, total of seven days) also gave a rather high molecular weight polymer ( M n = 1.15 × 10 4 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs) are thus the ideal solvents due to their lack of (or extremely low) vapor pressure, miscibility with polymers as well as organic compounds and metal catalysts (which makes most homogeneous catalytic reactions feasible), and high stability ranging from −30 to 300 °C. These promising characteristics of ILs enable us to consider them as desirable solvents for synthesis of high-molecular-weight polyesters in the ADMET condensation polymerization. Although olefin metathesis reactions in ILs have been known, the reported examples of ADMET polymerization have been limited so far. , For instance, the polymerization of 1,9-decadiene in 1- n -butyl-3-methyl imidazolium hexafluorophosphate ([Bmim]­PF 6 ,) in the presence of RuCl 2 (PCy 3 ) 2 (CHPh) ( G1 ) at 50 °C afforded rather high molecular weight polymers (Scheme , M n = 1.08–1.92 × 10 4 ) . The polymerization of 1,4-bis­(undec-10-en-1-yloxy)-triptycene conducted at 100 °C using G2 (initially 80 °C for 24 h, total of seven days) also gave a rather high molecular weight polymer ( M n = 1.15 × 10 4 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Pentanoic acid , and 1,4-pentanediol could be obtained from the hydrogenation of GVL. Moreover, the decarboxylation of GVL could produce a high yield of butenes over solid acid catalyst such as ZSM-5, Na-BETA, SiO 2 –Al 2 O 3 , and Al-SBA-15 . Recently, Lin et al found that a yield of >99% butenes could be achieved over a heteroatomic MFI-type zeolite (NbAlS-1) at ambient pressure under continuous flow conditions .…”
Section: Introductionmentioning
confidence: 99%
“…They found that 98 % butene yield could be obtained over the Nabate-5 catalyst after reacting 4.5 h at 300 °C. [10] Lin et al prepared a novel NbAlS-1 catalyst with both Lewis acids and Brønsted acid, 99 % butene yield can be obtained from 30 % GVL aqueous solution at 300 °C. [11] The same year, Ding and coworker prepared an amorphous SiO 2 À Al 2 O 3 (Si/Al = 4 : 1) catalyst, it also exhibits excellent catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…found that a high butene yield can be obtained only under the action of catalyst with large specific surface area and suitable amount of Brønsted acid sites [8b] . Subsequently, Bond, [9] Zhang, [10] Lin, [11] Ding, [8a] and their team all put forward their ideas on the reaction of catalyzing GVL to butene. Bond et al suggested that the ring‐open of GVL, cyclization and decarboxylation of pentanoic acids occur in parallel at Brønsted sites through a sequence of proton‐mediated elementary steps [9] .…”
Section: Introductionmentioning
confidence: 99%